Development of Historical Tourism Based on Augmented Reality (AR) and Virtual Reality (VR) at the Bongal International Historical Site, Central Tapanuli, North Sumatra, Indonesia - Ichwan Azhari; Lukitaningsih Lukitaningsih; Rosmaida Sinaga; Apriani Harahap; Syamsul Anuar Ismail (Diponegoro University, 2025)
In 2019, researchers have successfully discovered thousands of ancient artefacts at the Bongal Site. The ancient artefacts found were identified as originating from India, China, and the Middle East. This research aims to describe how the process of developing historical tourism at the Bongal International Site using Augmented Reality (AR) and Virtual Reality (VR) technology. The research method employed is Research and Development (R&D), which comprises three stages: pre-production, production, and post-production. The research results successfully led to the creation of a prototype for historical tourism at the Bongal International Site, utilising Augmented Reality and Virtual Reality technology. Artefacts that have been successfully created using AR/VR technology include Umayyah coins, Abbasid coins, cups, mini statues, and Amoghapasa statues. This research also succeeded in creating a 360o Virtual Tour application. The creation of AR/VR applications for the Bongal International Site is expected to enhance the site's landscape, making it more enjoyable and memorable for tourists.